Prolonged Withdrawal From Escalated Oxycodone Is Associated With Increased Expression of Glutamate Receptors in the Rat Hippocampus - Salisbury, Aaron J.; Blackwood, Christopher A.; Cadet, Jean Lud (Frontiers in Neuroscience, 2021)
People suffering from opioid use disorder (OUD) exhibit cognitive dysfunctions. Here, we investigated potential changes in the expression of glutamate receptors in rat hippocampi at 2 hours and 31 days after the last session of oxycodone self-administration (SA). RNA extracted from the hippocampus was used in quantitative polymerase chain reaction (qPCR) analyses. Rats, given long-access (9 hours per day) to oxycodone (LgA), took significantly more drug than rats exposed to short-access (3 hours per day) (ShA). In addition, LgA rats could be further divided into higher oxycodone taking (LgA-H) or lower oxycodone taking (LgA-L) groups, based on a cut-off of 50 infusions per day. LgA rats, but not ShA, rats exhibited incubation of oxycodone craving. In addition, LgA rats showed increased mRNA expression of GluA1-3 and GluN2a-c subunits as well as Grm3, Grm5, Grm6 and Grm8 subtypes of glutamate receptors after 31 days but not after 2 hours of stopping the SA experiment. Changes in GluA1-3, Grm6, and Grm8 mRNA levels also correlated with increased lever pressing (incubation) after long periods of withdrawal from oxycodone. More studies are needed to elucidate the molecular mechanisms involved in altering the expression of these receptors during withdrawal from oxycodone and/or incubation of drug seeking.